AB0641 Correlation between physicians and patients in the assessment of disease activity in systemic lupus erythematosus. (12th June 2018) - Nasa, Y.; Yokokawa, N.; Takahashi, H.; Takamasu, E.; Sugii, S.
Abstract : Background: In the assessment of systemic lupus erythematosus (SLE), laboratory data and clinical findings have been more focused than patient-reported outcomes which reflect quality of Life. Previous studies showed discrepancy between patients and physicians in assessments of disease activity in SLE. 1 The Systemic Lupus Activity Questionnaire (SLAQ), a lupus disease activity index which consisted of only patient reported outcomes, and SLE Disease Activity Index 2000 (SLEDAI-2K) were poorly corelated. 2 Objectives: We aimed to investigate the correlation between SLAQ and SLEDAI-2K scores in those who had discordance between patients' VAS and physicians' VAS or not. Methods: Both SLEDAI-2K and SLAQ were routinely measured at every outpatient visit in all SLE patients. We analysed the data between 9/12/2017 and 12/31/2017. Patients were divided into concordance(|patients' VAS-physicians' VAS|<25) or discordance group (|patients' VAS-physicains' VAS|≧25). 3 We measured correlation between SLAQ score vs SLEDAI-2K or SLEDAI-2K-nolab scores by Spearman's correlation in the concordance group and the discordance group. Comparison between the concordance group and the discordance group were perfomed using chi-squared test for categorical variables and Student t-test, Welch's t-test or Mann-Whitney U test for continuous variables. Results: Total 130 patients were analysed; 91% of female, a mean age (SD) of 44 15 years, steroid use of 91%, immunosuppressant use of 54%, HCQ use of 70%. Median SLAQ, SLEDAI-2K and SLEDAI-2K-nolab scores were 4 [IQR: 2–7], 4 [IQR: 2–4] and 0 [IQR: 0–2], respectively. Among them, 86 (66%) were classified in the concordance group. The SLAQ scores were weakly correlated with the SLEDAI-2K scores (ρ=0.228, p=0.009), and with SLEDAI-2K-nolab scores (ρ=0.352, p<0.001). In the concordance group, the SLAQ scores correlated with SLEDAI-2K scores (ρ=0.327, p=0.002) and SLEDAI-2K-nolab scores (ρ=0.523, p<0.001). The pain VAS and RAPID3 in the discordance group were significantly higher than those in the concordance group (30.77±26.54 vs 10.71±14.31, p<0.001, 8.11±5.87 vs 2.97±3.23, p<0.001, repectively). In the discordance group, the SLAQ scores were not correlated with SLEDAI-2K scores (ρ=−0.029, p=0.849) and with SLEDAI-2K-nolab scores (ρ=−0.083, p=0.957). Abstract AB0641 – Table 1: LLDAS: Lupus low Disease Activity State *Student t-test **Welch's t-test ¶Mann-Whitney U test Conclusions: The correlation between SLAQ vs SLEDAI-2K or SLEDAI-2K-nolab scores was exhibited in the concordance group. Musculoskeletal pain may be associated with the discordance between patients' and physicians' assessment. References: [1] Karlson EW, et al. Vlidation of a Systemic Lupus Activity Questionnaire(SLAQ) for population studies. Lupus2003;12:280–286. [2] Okamoto Y, et al. Validation of the Japanese version of the Systemic Lupus Activity Questionnaire that includes physician-based assessments in a large observational cohort. Lupus2016;25:486–495. [3] Barton JL, et al. Patient-physician discordance in assessments of a global disease severity in rheumatoid arthritis. Arthritis Care Res2010;62:857–64. Disclosure of Interest: None declared